KOMPETENSI MANAJERIAL KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DI SEKOLAH MENENGAH ATAS NEGERI 4 BATANGHARI PROVINSI JAMBI - Dahlia; Fransisko Chaniago; Salahuddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the principal’s managerial competence in improving teacher performance at SMA Negeri 4 Batanghari, Jambi Province. This research employed a qualitative descriptive approach using observation, interviews, and documentation as data collection techniques. The research informants consisted of the principal, vice principal, and teachers. Data analysis was carried out through data reduction, data presentation, and conclusion drawing, with source triangulation used to ensure data validity. The findings indicate that teacher performance has generally been implemented according to school regulations; however, it has not yet been optimal, particularly in lesson planning, instructional implementation, and learning evaluation. The obstacles to teacher performance include low discipline among some teachers and limited learning facilities and infrastructure. The principal’s managerial competence is manifested through program planning, task organization, teacher coaching, academic supervision, and motivation. These managerial efforts play an important role in improving teacher performance in a sustainable manner.